Assessment of active filter on transformers connected three phase bridge converters. Issue 4 (December 2020) - Kumar, Ritesh; Ramya Laxmi, D.; Shashi Kumar Reddy, Ravula.; Thirupathi, E.
Abstract: This paper starts with the benchmark analysis of shunt active power filter (SAPF) for adjustingeither compensations of harmonic current or compensating reactive power. Such equipment can capable of minimizing the content of harmonics present in the grid side generated by the non-linear loads. The proposed work represents the proficient responseof shunt active power filter for annihilates the contents of harmonics to keep the better quality of power supply.The implementation of SAPF on three-phase bridge (TPB) converters associated with cascaded single-stage transformers has been introduced.The transformers arrangements allow the compensator to utilize one dc-link unit that simplifies the management strategy and themode of operation. The system waveforms are provided by employing an appropriate pulse width modulation (PWM) technique having good co-relation with transformer turn ratio. System overview and easy maintenance create the projected SAPF has an efficient solution related with some standard previous configured model. The proposed model, PWM method and the control managements are given also as studies considering non-linear distortion and switching losses estimation. A MATLAB Simulink has been used to validate theImplementation of SAPF based on Cascaded Transformers Coupled with Three-Phase Bridge Converters.